Addressing sequelae of developmental regression associated with developmental disabilities: A systematic review of behavioral and educational intervention studies. (January 2019) - Sigafoos, Jeff; O'Reilly, Mark F.; Ledbetter-Cho, Katherine; Lim, Nataly; Lancioni, Giulio E.; Marschik, Peter B.
Highlights: Developmental regression is associated with a number of developmental disabilities. We reviewed 38 intervention studies addressing regression in cases of developmental disability. Twelve studies with 44 participants provided a convincing demonstration of a positive intervention effect. Positive results using behavioral interventions were noted for challenging behavior, communication, motor, and play skills. Future research should target the causes of regression and treatments for regression in autism spectrum disorder. Abstract: Developmental regression is characteristic of Rett syndrome and it also occurs in a number of other developmental disabilities. To assist clinicians in identifying promising therapeutic approaches, we identified 38 studies that sought to improve adaptive behavior functioning in cases where developmental regression had either already occurred or was likely to occur. Studies were summarized in terms of (a) participants, (b) intervention, (c) dependent variables, (d) outcomes, (e) study design, and (f) certainty of evidence. The available literature included 136 participants from preschoolers to adults. Most participants ( n  = 132) had Rett syndrome. Interventions targeted a range of dependent variables (e.g., challenging behavior, communication, motor, and play skills). Multi-component interventions derived from behavior analytic principles were the norm, suggesting the need for clinical expertise in the application of such principles. However, only 12 studies (with 44 participants) were rated as providing conclusive evidence of a positive intervention effect. Future research on the mechanisms underlying developmental regression might lead to new and more effective interventions.